Characterization of in vivo binding kinetics and non-displaceable binding of [18F]SynvesT-1 in the rat brain - Catriona Wimberley; Carlos J. Alcaide-Corral; Timaeus E. F. Morgan; Mark G. Macaskill; Bernadette Andrews; Holly McErlain; Valeria K. Burianova; Andrew Sutherland; Adriana A. S. Tavares (EJNMMI Research)
Abstract Background The synaptic vesicle glycoprotein 2 A (SV2A) has been identified as a biomarker of interest for neurological pathology. The SV2A specific radiotracer [18F]SynVesT-1 has shown good binding characteristics in mouse and human. The aim of this study was to characterize the binding parameters of [18F]SynVesT-1 in the rat brain and investigate simplified quantification methods. Twenty-one Positron Emission Tomography (PET) scans were conducted in male Sprague-Dawley rats with a bolus injection of [18F]SynVesT-1. Varying concentrations of non-radioactive SynVesT-1 were injected in an increasing mass dose paradigm (n = 21 ) with radioactivity in arterial blood recorded throughout. The radiometabolism was characterized in a further group (n = 7). The total volume of distribution (V T ) was estimated using compartmental modelling and Logan plot and then compared to the standardized uptake value at 30–60 min (SUV 30 − 60 ). Occupancy plots and a Lassen plot were generated. Results The pharmacokinetics of [18F]SynVesT-1 PET showed rapid brain uptake and increasing doses of SynVesT-1 revealed a robust reduction in radiotracer uptake over all brain regions. The two-tissue compartmental model was most appropriate and the estimated V T was highly correlated with Logan V T , as was the SUV 30 − 60 . The V ND was estimated to be 3.75, which is 12.5% (pons) to 22% (thalamus) of the V T . The estimated upper mass limit required to achieve 5% target occupancy is 0.48 µg/kg. Conclusion [18F]SynVesT-1 shows good characteristics for imaging the rat brain, however care must be taken to achieve adequate molar activity to avoid mass dose affects (< 5% occupancy). Data showed no suitable reference region for [18F]SynVesT-1, however SUV 30 − 60 does give an appropriate surrogate for V T . Clinical trial number Not applicable.